Conventional risk factors and arterial bed parameters in patients with coronary artery disease younger and older than 50 years - A. A. Khromova; L. I. Salyamova; O. G. Kvasova; V. E. Oleinikov (Кардиоваскулярная терапия и профилактика)
Aim. To study conventional risk factors and arterial stiffness parameters to identify non-invasive markers of coronary atherosclerosis in patients with and without history of cardiovascular disease, with premature and physiological vascular aging.Material and methods. The study included 198 patients with coronary artery disease (CAD) and 57 healthy people. The subjects were divided into two cohorts: younger and older than 50 years. Each group included patients with newly diagnosed acute coronary syndrome with/without history of cardiovascular disease (CAD and/or hypertension). Conventional risk factors were analyzed in all subjects. Ultrasound radiofrequency of common carotid arteries (CCA), applanation tonometry, volume sphygmography were performed.Results. Analysis of arterial parameters in individuals <50 years old revealed differences between healthy people and patients with CAD. In the subgroup of patients without a history of cardiovascular disease compared with healthy people, CCA were damaged in  77%  (p<0,05), aorta — in 13%, muscular arteries — in 29% (p<0,05); in patients with a history of cardiovascular disease, in 71% (p<0,05), 5% and 34% (p<0,05), respectively. In the older age group of patients with and without history of cardiovascular disease, CCA were damaged in 84% and 94% (p<0,05), aorta — in 92% and 87% (p<0,05), muscular arteries — in 42-44% (p<0,05), respectively. According to the ROC analysis, in patients <50 years old, the area under the curve (AUC) for the intima-media thickness (IMT) was 0,830, the threshold — 622,3 (p=0,000); for the  beta  stiffness index — 0,850, threshold — 7,01 (p=0,002); for L-/CAVI1 — 0,742, threshold — 7,3 (p=0,000). In patients >50 years of age, AUC for the IMT was 0,948, threshold — 607,5 (p=0,000); for the beta stiffness index — 0,740, threshold — 8,84 (p=0,000); for L-/CAVI1 — 0,861, threshold — 8,4 (p=0,000).Conclusion. Timely identification of atherosclerotic markers using noninvasive techniques can improve the prediction of cardiovascular events. A comprehensive non-invasive examination of the arteries with determination of IMT, beta stiffness index, and L-/CAVI1 will probably identify young people with an unfavorable absolute cardiovascular risk. .